Kinetics of hydrocarbon generation from the marine Ordovician Goldwyer Formation, Canning Basin, Western Australia - Johnson, Lukman M.; Rezaee, Reza; Smith, Gregory C.; Mahlstedt, N.; Edwards, D.S.; Kadkhodaie, Ali; Yu, H. (ELSEVIER, 2020)
Pyrolysis and bulk kinetic studies were used to investigate the hydrocarbon generation potential and source rock organofacies variability of marine organic-rich rocks from the Middle Ordovician (Darriwilian) Goldwyer Formation in the Canning Basin, Western Australia. Rock-Eval pyrolysis results for the analysed immature to mid-mature calcareous mudstones imply that the upper Goldwyer Sequence I contains oil-prone type I kerogen, while the lower Goldwyer Sequence III contains type II/III oil- and gas-prone kerogen. This is supported by pyrolysis gas chromatography (Py-GC) results that show the presence of homogenous organofacies in the Goldwyer Sequence I having aliphatic molecular signatures, possibly due to selective preservation of lipids derived from Gloeocapsomorpha prisca (G. prisca). The heterogeneous organofacies of the Goldwyer Sequence III contain aromatic moieties in similar abundance to the aliphatic compounds. The calcareous claystones of the Goldwyer Sequence I have the capacity to generate low wax paraffinic oil, whereas the Goldwyer Sequence III has potential for paraffinic-naphthenic-aromatic (P-N-A) low wax oils, gas, and condensate. The temperature for hydrocarbon generation for the type I kerogen, assuming a constant geological heating rate of 3 °C/my, is estimated to occur over a narrow interval between 145 °C and 170 °C for the Goldwyer Sequence I samples. Generation from the type II/III kerogen occurs from 100 °C to 160 °C in the Goldwyer Sequence III samples which are significantly less thermally stable than the Goldwyer Sequence I samples. The kinetic results for both sequences were used in standard thermal and burial history plots to evaluate their transformation ratio and hydrocarbon generative potential. This provided basin-specific kinetic inputs for burial history modelling and better constraint on kerogen transformation and hydrocarbon generation on the Broome Platform.